Effectiveness of rhizobia nodulating recent promiscuous soyabean selections in the moist savanna of Nigeria - Sanginga, P.; Thottappilly, G.; Dashiell, Kenton E. (Elsevier, 2000)
The ability of soybean to nodulate with a wide range of indigenous bradyrhizobia has been used in a breeding programme since 1997 in Nigeria. As far as is known, these indigenous bradyrhizobia strains have not been tested for compatibility and effectiveness with recent selections from a breeding programme which has proceeded without input from soil microbiologists for the last 20 yr. Twenty bradyrhizobia strains isolated from soyabean and cowpea grown in Ibadan and Zaria soils in Nigeria were examined in a pot experiment for symbiotic effectiveness on two promiscuous soyabean breeding lines (TGX 1660-19F and TGX 1456-2E) and a cowpea cultivar (IT 849-92). Two bradyrhizobial isolates (R25B and IRj 2180A) had an average symbiotic effectiveness (SE) of 2.36-fold and 1.62-fold of the uninoculated control when inoculated on 1456-2E and 1660-19F, respectively. These strains, however, were less effective on cowpea having a SE of 1.20-fold. Cowpea bradyrhizobia inoculated on promiscuous soyabeans produced less than 77 nodules plant−1 compared to an average of 120 by the two best bradyrhizobia strains from soyabean. The best isolates (R25B, IRj 2180A and their mixture) and one cowpea bradyrhizobia (IRc 461) were further tested on these lines under field conditions at three sites in different agroecological zones in moist savanna (Fashola, Mokwa and Zaria) in Nigeria. Both soyabean lines nodulated with the local rhizobia, but the degree of effectiveness depended on the plant genotype and field sites. Soyabean line 1456-2E showed improved growth and yield in response to N fertilizer application indicating that in this line N2 fixation induced by the indigenous bradyrhizobial community supplied less than optimal amounts of N. The mixture of bradyrhizobial isolates R25B and IRj 2180A increased grain yield of 1456-2E by 30 and 25% at Zaria and Mokwa but failed to do so at Fashola. Grain yield of 1660-19F was not affected by bradyrhizobial inoculation and N fertilizer at any of the three sites. Thus, the need for bradyrhizobia inoculation will be determined by the degree of promiscuity of soybean lines and the effectiveness of the community of indigenous bradyrhizobia present in the site.